Comparison of Two Commercially Available Immunoassays for the Measurement of Bovine Cardiac Troponin I in Cattle With Induced Myocardial Injury - Smith, Joe S.; Varga, Anita; Schober, Karsten E. (Frontiers in Veterinary Science, 2020)
Background: Multiple cardiac troponin I (cTnI) immunoassays are commercially available. Overall, assays have not been standardized, and inter-assay differences in the detection of the analyte cardiac troponin I can be clinically relevant. Objective: To compare the diagnostic accuracy of the commercially available Abbott i-STAT®1 cTnI immunoassay (i-STAT) and the previously validated ADVIA Centaur TnI-Ultra immunoassay (Centaur) in cattle. Hypothesis: There will be significant differences in bovine serum cTnI results measured by the Centaur and i-STAT methods. Animals: Ten dairy cows with experimentally induced myocardial injury due to monensin administration. Thirty apparently healthy dairy cows with no history of monensin exposure served as controls. Methods: Blood was collected at various time points after administration of a single dose of monensin (20 to 50 mg/kg) via orogastric tube. A total of 112 blood samples were collected. Cardiac TnI concentration was analyzed with the two methods and the association between methods analyzed via linear regression. Bland-Altman analysis to evaluate agreement between methods was performed on samples divided into groups (cTnI < 1.0 ng/mL and cTnI ≥ 1.0 ng/mL). Results: Analyzer results were linearly correlated with each other (R2 = 0.931). Samples with cTnI concentrations < 1.0 ng/mL had a bias of -0.13 ± 0.20 ng/mL and samples with cTnI concentrations > 1.0 ng/mL had a bias of -9.81 ± 13.26 ng/mL. Conclusions and clinical importance: The results of this study reveal that cTnI concentrations determined with the i-STAT are systematically lower compared to the concentrations determined by the Centaur.